2004
DOI: 10.1177/1054773804267878
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease Self-Management Improved with Enhanced Self-Efficacy

Abstract: This pilot study used a quasi-experimental pretest-posttest design to examine if participation in a chronic disease self-management program (CDSMP) improved self-efficacy, self-efficacy health, and self-management behaviors in an underserved, poor, rural population. The sample, recruited from two clinics in a south central state, consisted of 48 adults (59.70 +/- 11.22 years) and was 79.2% Caucasian (n = 38) and 20.8% (n = 10) African American. Trained lay leaders with chronic illnesses directed the interactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 13 publications
2
69
2
Order By: Relevance
“…These factors should also be taken into account explicitly in targeting and evaluating programs. 89 Motivation is a key component of any self-management intervention. For successful self-management, not only should participants feel that an intervention is relevant to the problems they are experiencing, but also they should be motivated to engage with the intervention in practice and over time.…”
Section: Psychological Issues In Prostate Cancer Related To Developmementioning
confidence: 99%
“…These factors should also be taken into account explicitly in targeting and evaluating programs. 89 Motivation is a key component of any self-management intervention. For successful self-management, not only should participants feel that an intervention is relevant to the problems they are experiencing, but also they should be motivated to engage with the intervention in practice and over time.…”
Section: Psychological Issues In Prostate Cancer Related To Developmementioning
confidence: 99%
“…Although the clinics were able to increase measures of patient care, patient outcomes were not significantly affected. In addition, a study of a rural sample of 48 adults with at least one chronic disease found that following a 6-week program, patients were able to improve their ability to self manage their symptoms and disease [10]. In contrast, Bayliss et al [13] investigated barriers to self-care and reported that over 90% of respondents indicated their physical limitations due to the chronic condition, and multiple chronic conditions, were barriers to exercise to improve their chronic condition.…”
Section: Introductionmentioning
confidence: 99%
“…Overweightness and obesity continue to rise among both adults and children, increasing the prevalence of chronic diseases in both groups. Multiple programs have been initiated to combat these health disparities, with differing levels of success [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…217 In chronic disease management, self-efficacy has been reported to be influential in the success of self-management. 218,222,223 Fortunately, self-efficacy can be positively influenced with intervention, and should therefore be promoted in the management of chronic disease. [223][224][225] Self-efficacy is built when a person experiences success in using a skill, witnesses others successfully using a skill, or receives verbal persuasion and encouragement.…”
Section: Self-efficacy Pd Is a Chronic Condition Which Requires The mentioning
confidence: 99%
“…218,222,223 Fortunately, self-efficacy can be positively influenced with intervention, and should therefore be promoted in the management of chronic disease. [223][224][225] Self-efficacy is built when a person experiences success in using a skill, witnesses others successfully using a skill, or receives verbal persuasion and encouragement. 221,226 A maintenance program for communication in PD is therefore integral to the holistic management plans of people with PD.…”
Section: Self-efficacy Pd Is a Chronic Condition Which Requires The mentioning
confidence: 99%